Determination of Total Flavonoid Contents and Antioxidant Activity of Leucaena Leucocephala Leaves's Extract - Taupik Hidayat; Baharuddin Hamzah; Minarni R. Jura (Universitas Tadulako, 2020)
The study of the determination of total flavonoid contents and antioxidant activity of extract of Leucaena leucocephala leaves had been carried out using UV-Vis spectrophotometry method. This study aimed to determine the total flavonoid contents and the antioxidant power of Leucaena leucocephala extract. Extraction of chemical content from Leucaena leucocephala was carried out by the maceration method using absolute ethanol. The total flavonoid contents from the sample extract were taken up for absorption at wavelength 510 nm and 700 nm. The variation of the concentration of Leucaena leucocephala leaves' extract was respectively 20, 40, 60, and 80 ppm. The results of the study showed that the total flavonoid contents of extracts of Leucaena leucocephala leaves was 2.242 g/100 grams. The antioxidant activity of Leucaena leucocephala leaves extract was carried out using DPPH (1,1-diphenyl-2-picrylhydrazine) and the measurement of absorption was at a wavelength of 517 nm, and by varying the sample concentration. Positive control used was vitamin C solution with the same variation of extract's concentration. The results showed that the IC50 values of Leucaena leucocephala leaves extract and vitamin C were 175.388 and 28.907 ppm. Based on the IC50 data it can be stated that the antioxidant vitamin C was stronger than the Leucaena leucocephala leaves extract which was classified as a weak type of natural antioxidant.